Conduction and stability performance of CsH2PO4 with NaH2PO4/ZrO2 for fuel cell. (10th November 2021) - Veer, Dharm; Kumar, Pawan; Singh, Deshraj; Kumar, Devendra; Katiyar, Ram S
Abstract: Solid acid composites of CsH2 PO4 /NaH2 PO4 /ZrO2 with different weight ratios of CsH2 PO4 (CDP), NaH2 PO4 (SDP), and ZrO2 were synthesized and characterized. The characterizations of the solid acid composite were carried out for determining structure, thermal stability, and conductivity, utilizing x-ray Diffraction, Fourier Transform Infrared Spectroscopy, Thermogravimetric analysis, Differential Thermal Analysis, and conductivity measurements. The composite powders were in the form of pellets of 4 mm thickness for conductivity measurement. SDP in the composites has a large effect on the conductivity measurement and this material increased the low-temperature conductivity of CDP by up to 1.5 orders of magnitude. The superprotonic transition was identified at temperatures from 220 to 270 °C in CDP/SDP/ZrO2 composites under atmospheric pressure. The thermal stability of the solid acid composites for dehydration, melting, and decomposition was investigated in the temperature range of 50 to 300 °C under environments with atmospheric humidification.